Perovskite solar cells : technology and practices - Fu, Kunwu (Oakville, ON, Canada ; Waretown, NJ, USA : Apple Academic Press, 2019)
The increasing use of metal halide perovskites as light harvesters has stunned the photovoltaic community. The book, Perovskite Solar Cells: Technology and Practices, covers the basics and provides up-to-date research in the field of perovskite photovoltaics--a fast trending branch of the thin film photovoltaic generation. This comprehensive handbook provides a broad and overall picture of perovskite solar cells (PSCs), starting with the history of development and revolution of PSCs. The authors then delve into electron-transporting materials, hole-transporting materials, and lead-free alternatives. An important chapter on tandem solar cells is also included. The chapters discuss how different layers in PSCs are fabricated and function and how their roles are as important as the perovskite layer itself. It explores what has been done and what can probably be done to further improve the performance of this device.
Structure and properties of perovskites -- Typical configurations of perovskite solar cells -- Current status of high-efficiency solar cells -- Durability and stability of perovskite solar cells -- Metal oxides as electron selective contact -- Organic n-type materials -- Organichole transporting materials -- Inorganichole transporting materials -- Hole transporting free perovskite solar cells -- Tin-based perovskites -- Germanium-based perovskites -- Copper-based perovskites -- Double perovskites -- Bismuth-based perovskites -- Antimony-based perovskites -- Perovskite tandem solar cells for photovoltaics -- Life cycle assessments -- Commercial prospects, and manufacturing costs.
OCLC-licensed vendor bibliographic record.
Keywords: Solar cells -- Materials; Photovoltaic cells -- Materials; Perovskite; TECHNOLOGY & ENGINEERING / Mechanical; SCIENCE / General; TECHNOLOGY / Power Resources